2023
DOI: 10.3389/fmed.2023.1036393
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of elective surgery and associated factors among patients scheduled for elective surgeries in public hospitals in Harari regional state, Eastern Ethiopia

Abstract: BackgroundCanceling elective surgeries is a significant problem in many hospitals leading to patient dissatisfaction, increased costs, and emotional trauma for patients and their families. Despite this, there is limited information about the cancellation of elective surgeries in Ethiopia, mainly in the study area.ObjectiveThis study aimed to assess the magnitude of cancellation and associated factors among patients scheduled for elective surgeries in public hospitals in the Harari Regional State, Eastern Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Female participants had a 2.46 times higher cancellation rate for elective surgery than male participants. Patients with high blood pressure had a 5.09 times higher chance of canceling surgery than those without high blood pressure (13). An study in Singapore reported that elective surgery cancellation rates in people with high blood pressure were higher than in normal people (14).…”
Section: Discussionmentioning
confidence: 97%
“…Female participants had a 2.46 times higher cancellation rate for elective surgery than male participants. Patients with high blood pressure had a 5.09 times higher chance of canceling surgery than those without high blood pressure (13). An study in Singapore reported that elective surgery cancellation rates in people with high blood pressure were higher than in normal people (14).…”
Section: Discussionmentioning
confidence: 97%